Removal of the navicular bone with wedge osteotomy of the cuboid bone as a method of surgical treatment of cavus foot. Clinical case - V. S. Apresyan; L. G. Makinyan; A. M. Mannanov; Ch. K. Moldamyrzaev; D. A. Samkovich (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
Relevance. Midfoot osteotomies are common surgical treatment option for the pes cavus in the presence of a deformity apex in the area of the Chopard joint. Most midfoot osteotomies require additional surgeries: release of the plantar fascia, tendon transfer, etc. Also, osteotomies have typical complications, such as nonunion of the osteotomy area, insufficient or excessive deformity correction. We used a new method for correcting the deformity of the pes cavus – removal of the navicular bone with wedge-shaped osteotomy of the cuboid bone.Aim: analyze the results of a patient who underwent removal of the navicular bone with wedge osteotomy of the cuboid bone.Object and methods. in 2020, we performed the correction of the pes cavus deformity by removing the navicular bone and wedge-shaped osteotomy of the cuboid bone. Clinical outcomes were assessed based on foot appearance, joint function, AOFAS scores, and radiographic findings. Results. Follow-up period was 36.8 months. The healing time was 6 weeks. After this surgical intervention, there was an improvement in functional results, as well as a good aesthetic result. At the last visit, the mean AOFAS score was 88/100. Meary angle, calcaneus angle and Hibb angle were close to normal and changed from 26° to 5°, from 44° to 28° and from 66° to 41°, respectively. In the other joints of the foot, no degenerative changes were  detected during  the  observation  period.  Subjectively,  the  patient  was satisfied with the results of the operation. Objective results were rated as excellent.Conclusion. Removal of the navicular bone with cuboid wedge osteotomy is an effective surgery for pes cavus. When using this technique, the risk of developing arthrosis and stiffness of the adjacent joints is lower and there is no effect on the mobility of the ankle joint. Additional studies are required to investigate the safety of this technique, as well as to assess the long-term results of treatment.